TIPS DIET DALAM AL-QUR'AN (Telaah Penafsiran Qs. Al-Hajj (22): 27 di Akun IG @quranreview) - Annisa', Anni; Sulistiyawati, Eka (El-Waroqoh : Jurnal Ushuluddin dan Filsafat, 2025)
This study aims to examine dietary tips found in the Qur’an through the interpretation of Surah Al-Hajj (22:27), focusing on the application of dietary principles in the context of health and eating habits. The research uses a qualitative method with a library research approach, which involves an in-depth review of interpretations and relevant Islamic sources. The author analyzes the meaning and message contained in this verse and relates it to the concept of healthy eating in Islam. The results of the study indicate that the Qur’an provides guidance on the importance of maintaining the body and a balanced diet, as well as self-control in food consumption. These findings are presented on the Instagram platform @quranreview, which offers an easy-to-understand interpretation and highlights the relevance of the Qur'anic message to modern healthy lifestyles. The study concludes that the Qur’an offers practical guidelines for maintaining body health through a balanced diet approach, which includes regulating eating habits, moderation, and seeking blessings in every action.